Novel predictive factors scoring model for persistent hypertension after adrenalectomy in patients with primary aldosteronism - Kawintharat Harirugsakul; Swiss Suharitdumrong; Kamol Panumatrassamee; Supoj Ratchanon; Manint Usawachintachit; Dutsadee Sowanthip; Pea Pobpan; Gantapong Sainont; Apirak Santingamkun (Scientific Reports)
Abstract Primary aldosteronism (PA) is the most common endocrinologic hypertension, affecting 3.9–15% of hypertensive patients. While unilateral PA is potentially curable through adrenalectomy, a significant proportion of patients experience persistent hypertension despite successful surgery. This study developed and validated a novel predictive scoring model for persistent hypertension following adrenalectomy based on 363 patients from a 25-year single-center experience. Persistent hypertension occurred in 59.5% of patients postoperatively. Multivariable analysis identified five independent predictors: age ≥ 50 years, dyslipidemia, BMI ≥ 25 kg/m2, use of ≥ 3 antihypertensive medications, and hypertension duration ≥ 5 years. The model demonstrated excellent discriminative ability with area under the curve of 0.81 in internal validation and 0.72 in external validation. Predictive risk scores were categorized into low-risk (0–1), intermediate-risk (2–3), and high-risk (4–5) groups, with persistent hypertension rates of 23.5%, 72.1%, and 90.6%, respectively. This practical scoring system enables improved preoperative counseling and individualized management planning using readily available clinical parameters.